ANALISIS KECERDASAN MUSIKAL ANAK USIA DINI DENGAN BERMAIN ALAT MUSIK ANGKLUNG DI KELOMPOK B - Ari Patma Sari; Dwi Prasetiyawati Diyah Hariyanti; Purwadi Purwadi (Wawasan Pendidikan, 2021)
Musical intelligence is musical intelligence which is characterized by a person's ability in the field of music, both sensitivity and mastery of tones, rhythms, rhythm patterns, instruments, and musical expressions, so that a person can play musical instruments or sing songs. This study aims to analyze the musical intelligence of early childhood with angklung musical instruments in Hidayatullah Islamic Kindergarten Semarang. The benefit of this research is knowing how to apply the angklung musical instrument correctly so that it can develop children's musical intelligence. The method used is descriptive qualitative research with data collection methods, namely observation, interviews, and documentation. Based on the results of research that has been done that the activity of playing angklung musical instruments can play an active role in stimulating children's musical intelligence. This can be seen when playing angklung musical instruments, children have skills in playing angklung musical instruments, the ability to adjust the tempo, adjust the tone, adjust the rhythm/rhythm, and the ability to sing short songs with the right rhythm. The results of the study showed that the musical intelligence of children in group B of Hidayatullah Islamic Kindergarten Semarang through playing the angklung musical instrument developed as expected.